In situ reduction of silver nanoparticles in the lignin based hydrogel for enhanced antibacterial application - Li, Man; Jiang, Xingxing; Wang, Dan; Xu, Zeyu; Yang, Minghui (Colloids and surfaces, B, Biointerfaces, 2019)
[Display omitted] •Lignin based antimicrobial hydrogel was synthesized for antimicrobial application.•Silver nanoparticles were incorporated to enhance the antimicrobial effect.•The hydrogel shows good antibacterial properties towards both S. aureus and E. coli.•The hydrogel displays low toxicity to cells. Although antibiotics have been widely used, the problem of bacterial infection in the medical field still faces many challenges. In this study, we designed a new lignin based antimicrobial hydrogel for antimicrobial application. First, we grafted the amino group onto sodium lignin sulfonate through Mannich reaction to obtain lignin amine (LA), which can cross-link with poly(vinyl alcohol) (PVA) to form hydrogel. Then, silver nitrate solution is added to the formed gel pre-solution to be in situ reduced to silver nanoparticles. The enhanced effect of antibacterial properties due to lignin and silver nanoparticles endows the hydrogel enhanced antibacterial properties. The modification of sodium lignosulfonate and the crosslinking reaction between LA and PVA are confirmed by FTIR, while the content of nitrogen in LA is characterized by XPS. The SEM image of the hydrogel after lyophilization illustrates its internal porous network structure. The rheological test of hydrogel demonstrates its good strength and elasticity. The hydrogel exhibits good antibacterial properties in in vitro antibacterial experiments towards both S. aureus and E. coli, while toxicity tests using L929 cells demonstrated good biocompatibility of the hydrogel.